Farmers' Preferences For Bluetongue Vaccination Scheme Attributes: An Integrated Choice and Latent Variable Approach. (21st November 2017) - Sok, Jaap; van der Lans, Ivo A.; Hogeveen, Henk; Elbers, Armin R. W.; Oude Lansink, Alfons G. J. M.
Abstract: Re‐emergence of the bluetongue disease in Europe poses a continuous threat to European livestock production. Large‐scale vaccination is the most effective intervention to control virus spread. Compared to command‐and‐control approaches, voluntary vaccination approaches can be effective at lower costs, provided that farmers are willing to participate. We use a discrete choice experiment to estimate the preferences for vaccination scheme attributes, accounting for preference heterogeneity via an integrated choice and latent variable approach. In designing livestock disease control schemes, it is often argued that governments should use financial, incentive‐based policy instruments to compensate farmers for externalities, assuming they act in rational self‐interest. Our results suggest that in addition to economic motives, farmers can have intrinsic or social motives to invest in livestock disease control. Implications for the effectiveness of providing subsidy or information to motivate voluntary participation are discussed.